Predictors of Failure of Closure in Percutaneous EVAR Using the Prostar XL Percutaneous Vascular Surgery Device. Issue 1 (January 2015) - Rijkée, M.P.; Statius van Eps, R.G.; Wever, J.J.; van Overhagen, H.; van Dijk, L.C.; Knippenberg, B.
Abstract : Objective: To identify predictors of failure in percutaneous endovascular aneurysm repair (P-EVAR) using the Prostar XL Percutaneous Vascular Surgery Device (Abbot Vascular, Santa Clara, CA, USA) and the need for conversion to conventional femoral cutdown (O-EVAR). Methods: Consecutive patients who underwent P-EVAR with the Prostar XL device between January 2009 and April 2012 were included in this series. Patients with a circular calcified common femoral artery (CFA) on computed tomography angiography were operated using O-EVAR and were therefore excluded. To identify predictors of success of closure in P-EVAR, artery characteristics, sheath size used, and comorbidities were analyzed in a univariate logistic regression model. Results: Percutaneous access was achieved in 154 femoral access sites with conversion to O-EVAR was needed in 10 (6.5%). Significant predictors of conversion included sheath size (continuous, relative risk [RR] 1.50, p  < .03) and the ratio between sheath size and CFA diameter >0.75 (RR 8.93, p  < .01). Variables such as calcification quantity scores, CFA diameter, body mass index, and comorbidities were not significant. Conclusion: The data demonstrate that sheath size, in particular, combined with CFA diameter predicts failure of closure in P-EVAR using the Prostar XL device. This ratio can be utilized to help in decision making with regard to the EVAR approach. A ratio of >0.75 would favor a primary open groin approach.